Soil organic carbon under conservation agriculture in Mediterranean and humid subtropical climates: Global meta‐analysis. (2nd February 2023) - Tadiello, Tommaso; Acutis, Marco; Perego, Alessia; Schillaci, Calogero; Valkama, Elena
Abstract: Conservation agriculture (CA) is an agronomic system based on minimum soil disturbance (no‐tillage, NT), permanent soil cover, and species diversification. The effects of NT on soil organic carbon (SOC) changes have been widely studied, showing somewhat inconsistent conclusions, especially in relation to the Mediterranean and humid subtropical climates. These areas are highly vulnerable and predicted climate change is expected to accentuate desertification and, for these reasons, there is a need for clear agricultural guidelines to preserve or increment SOC. We quantitively summarized the results of 47 studies all around the world in these climates investigating the sources of variation in SOC responses to CA, such as soil characteristics, agricultural management, climate, and geography. Within the climatic area considered, the overall effect of CA on SOC accumulation in the plough layer (0–0.3 m) was 12% greater in comparison to conventional agriculture. On average, this result corresponds to a carbon increase of 0.48 Mg C ha −1 year −1 . However, the effect was variable depending on the SOC content under conventional agriculture: it was 20% in soils which had ≤ 40 Mg C ha −1, while it was only 7% in soils that had > 40 Mg C ha −1 . We proved that 10 years of CA impact the most on soil with SOC ≤ 40 Mg C ha −1 . For soils with less than 40 Mg C ha −1, increasing the proportion of crops with bigger residue biomasses in a CA rotation was a solution to increase SOC. The effect of CA on SOC depended on clay content only in soils with more than 40 Mg C ha −1 and become null with a SOC/clay index of 3.2. Annual rainfall (that ranged between 331–1850 mm y −1 ) and geography had specific effects on SOC depending on its content under conventional agriculture. In conclusion, SOC increments due to CA application can be achieved especially in agricultural soils with less than 40 Mg C ha −1 and located in the middle latitudes or in the dry conditions of Mediterranean and humid subtropical climates. Highlights: The results of 47 studies were quantitively summarized by using a meta‐analysis SOC accumulation due to CA was 12% greater compared to conventional agriculture SOC increment due to CA can reach 20% in soils having less than 40 Mg C ha −1 The impacts of pedo‐climatic factors and agronomic management practices were studied